Optimizing The Hydrolysis Acid Process Of Cellulose From Post-Harvest Sugarcane (Saccharum Officinarum) Residue For Bioethanol Production - Alivia Alfiarty (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Tons of post-harvest sugarcane is produced in Indonesia as agricultural residue. This lignocellulosic material is a potential source of second generation ethanol production. Diluted acid hydrolysis is one of the most efficient pre-treatments for hemicellulosic solubilization. The hydrolysate content is rich in glucose, which can be converted to ethanol by yeast or other micro-ogranism. This work measures the impact various methods of diluted acid hydrolysis (acid concentration, solid: liquid ratio) have on glucose concentration in hydrolysate. Statistical analysis was used to determine the most efficent formule to increase glucose concentrations. An acid concentration of 0,6 M, an S:L ratio of 5:100 (g:ml) with steam explosure was established and validated as the optimum pre-treatment conditions for the acid hydrolysis process. Under such conditions, hydrolysate with 25 % of glucose was obtained.